1975
DOI: 10.1530/jrf.0.0420187
|View full text |Cite
|
Sign up to set email alerts
|

The Inability of Dibutyryl Adenosine 3',5'-Monophosphate to Induce the Decidual Reaction in Intact Pseudopregnant Mice

Abstract: The technique for assessing the ability of a compound to initiate the decidual response is simple and conclusive. It involves introducing the compound in solution into the uterine lumen of an intact rat or mouse during the`sensitive period' of pseudopregnancy (Finn & Keen, 1963;Hetherington, 1968). This technique was used to compare the ability of arachis oil, phosphate-buffered saline (PBS; Dulbecco & Vogt, 1954) and dibutyryl adenosine 3',5'-monophosphate (dibutyryl cyclic AMP\p=m-\dcAMP) to initiate the dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Intraluminal injections of histamine failed to trigger a DCR in hormonally primed immature rabbits (Elton, 1966) and our results were inconclusive. As reported for mice (Webb, 1975), dcAMP was ineffective in inducing a DCR in rabbits.…”
Section: Discussionsupporting
confidence: 75%
“…Intraluminal injections of histamine failed to trigger a DCR in hormonally primed immature rabbits (Elton, 1966) and our results were inconclusive. As reported for mice (Webb, 1975), dcAMP was ineffective in inducing a DCR in rabbits.…”
Section: Discussionsupporting
confidence: 75%
“…Histamine is known to be re¬ leased during early oestrogen action (Spaziani & Szego, 1958;Shelesnyak, 1959a;McKercher, Van Orden, Bhatnagar & Burke, 1973) and uterine histamine levels fall at the time of implantation (Shelesnyak, 1959b). These observations led Shelesnyak, Marcus & Lindner (1970) to suggest a role for histamine as the mediator of the decidual stimulus, but both histamine (see Finn, 1971) and cyclic AMP (Webb, 1975b) have now been shown not to be involved in evoking the response. On the other hand, the present results are compatible with a role for histamine in sensitization of the uterus in preparation for the decidual response, an idea supported by the observations of Ferrando & Nalbandov (1968) who showed that implantation could not take place in the absence of uterine mast cells which are the only known source of uterine histamine (McKercher et ai, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…A rapid but transient increase in cyclic AMP and cyclic GMP in uterine tissue following oil-induced decidualization indicated their involvement in the early events leading to decidual cell formation (Ledford, Rankin & Baggett, 1975;Rankin, Ledford & Baggett, 1977). In the rat, mouse and rabbit, however, neither intraperitoneal injection nor intraluminal application of cyclic AMP or dibutyryl cyclic AMP (dbcAMP) were effective in inducing deciduoma or the implantation of diapausal blastocysts (Leroy, Vansande, Shetgen & Brasseur, 1974;Webb, 1975a;Holmes & Bergstrom, 1976;Hoffman et al, 1977;Rankin et al, 1977;Wu & Chang, 1977). Fisher & Gunaga (1975) have reported that blastocyst development was retarded when cyclic AMP accumulation was induced following incubation with theophyUine to inhibit the intracellular breakdown of cyclic AMP.…”
Section: The Interaction Between Embryo and Endometrium At Implantationmentioning
confidence: 99%